THE EFFECTIVENESS OF FLASH SALES AND ELECTRONIC WORD-OF-MOUTH ON CONSUMER BEHAVIOR: A QUANTITATIVE STUDY OF SHOPEE USERS IN PEKANBARU CITY - Fakhri Hidayat; Aida Nursanti; Agnes Alvionita; Prima Andreas Siregar (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
This study aims to analyze the influence of Flash Sale promotions and electronic word-of-mouth (eWOM) on the purchase decisions and customer satisfaction of Shopee platform users in Pekanbaru City. This study employed a quantitative method with a Structural Equation Modeling (SEM) approach using SmartPLS 4.0. The sample consisted of 140 respondents who were Shopee users in Pekanbaru City and had made at least one purchase. The results indicate that Flash Sale promotions and eWOM have a positive and significant impact on purchase decisions. Purchase decisions also have a positive and significant effect on customer satisfaction. Additionally, purchase decisions significantly mediate the relationship between Flash Sale promotions, eWOM, and customer satisfaction. Thus, the more effective the Flash Sale promotions and the stronger the influence of eWOM, the higher the level of purchase decisions and customer satisfaction. Penelitian ini bertujuan untuk menganalisis pengaruh promosi Flash Sale dan electronic word-of-mouth (eWOM) terhadap keputusan pembelian dan kepuasan pelanggan pengguna platform Shopee di Kota Pekanbaru. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan Structural Equation Modeling (SEM) menggunakan SmartPLS 4.0. Sampel penelitian terdiri dari 140 responden yang merupakan pengguna Shopee di Kota Pekanbaru yang telah melakukan setidaknya satu kali pembelian di platform tersebut. Hasil penelitian menunjukkan bahwa promosi Flash Sale dan eWOM memiliki pengaruh positif dan signifikan terhadap keputusan pembelian. Keputusan pembelian juga memiliki pengaruh positif dan signifikan terhadap kepuasan pelanggan. Selain itu, keputusan pembelian secara signifikan memediasi hubungan antara promosi Flash Sale, eWOM, dan kepuasan pelanggan. Dengan demikian, semakin efektif promosi Flash Sale dan semakin kuat pengaruh eWOM, semakin tinggi tingkat keputusan pembelian dan kepuasan pelanggan.